Let's simplify the expression step by step:
-
Evaluate the square root of 64: \[ \sqrt{64} = 8 \]
-
Evaluate \(3^{\sqrt{64}}\): \[ 3^{\sqrt{64}} = 3^8 \] Now, calculate \(3^8\): \[ 3^8 = (3^4)^2 = 81^2 = 6561 \]
-
Evaluate \(2^2\): \[ 2^2 = 4 \]
-
Compute \(2^2 + 5\): \[ 2^2 + 5 = 4 + 5 = 9 \]
-
Take the square root of the result: \[ \sqrt{2^2 + 5} = \sqrt{9} = 3 \]
-
Multiply by 3: \[ 3 \cdot \sqrt{2^2 + 5} = 3 \cdot 3 = 9 \]
-
Combine the results: \[ 3^8 + 3 \cdot \sqrt{2^2 + 5} = 6561 + 9 = 6570 \]
Thus, the simplified expression is: \[ \boxed{6570} \]